General orthopaedics: a hospitalist rotation. Issue 1 (January 2018) - Crenshaw, Andrew H.; Strickland, Carson D.; Ochsner, Mims G.
Abstract : The general orthopaedic rotation for residents covers not only orthopaedic conditions in geriatrics, such as hip or femoral fractures or infected total joints, but also exposes residents to orthopaedic conditions such as infection, compartment syndrome, spinal disorders, foot and ankle fractures, and elective total joint replacements. By the end of their postgraduate education year-2 (PGY-2) rotation, residents are confident in managing the postoperative care of patients, evaluating new patients, and performing basic operative procedures (closed reduction, and intramedullary nailing of long-bone fractures, irrigation and debridement, etc). The resident on a PGY-4 general orthopaedic rotation will be required to lead and manage the orthopaedic team. During that rotation, the resident will gain sufficient knowledge to operate independently on routine procedures. This is a leadership milestone that ushers in the PGY-5 year.